Epidemiology and population structure of Haemophilus influenzae causing invasive disease. Issue 12 (13th December 2021) - Carrera-Salinas, Anna; González-Díaz, Aida; Calatayud, Laura; Mercado-Maza, Julieta; Puig, Carmen; Berbel, Dàmaris; Càmara, Jordi; Tubau, Fe; Grau, Imma; Domínguez, M. Ángeles; Ardanuy, Carmen; Martí, Sara
Abstract : This study provides an update on invasive Haemophilus influenzae disease in Bellvitge University Hospital (2014–2019), reporting its evolution from a previous period (2008–2013) and analysing the non-typeable H. influenzae (NTHi) population structure using a clade-related classification. Clinical data, antimicrobial susceptibility and serotyping were studied and compared with those of the previous period. Population structure was assessed by multilocus sequence typing (MLST), SNP-based phylogenetic analysis and clade-related classification. The incidence of invasive H. influenzae disease remained constant between the two periods (average 2.07 cases per 100 000 population), while the 30 day mortality rate decreased (20.7–14.7 %, respectively). Immunosuppressive therapy (40 %) and malignancy (36 %) were the most frequent comorbidities. Ampicillin and fluoroquinolone resistance rates had increased between the two periods (10–17.6 % and 0–4.4 %, respectively). NTHi was the main cause of invasive disease in both periods (84.3 and 85.3 %), followed by serotype f (12.9 and 8.8 %). NTHi displayed high genetic diversity. However, two clusters of 13 ( n =20) and 5 sequence types (STs) ( n =10) associated with clade V included NTHi strains of the most prevalent STs (ST3 and ST103), many of which showed increased frequency over time. Moreover, ST103 and ST160 from clade V were associated with β-lactam resistance. Invasive H. influenzae disease is uncommon, but can be severe, especially in the elderly with comorbidities. NTHi remains the main cause of invasive disease, with ST103 and ST160 (clade V) responsible for increasing β-lactam resistance over time.